2017
DOI: 10.5455/njppp.2017.7.0413713052017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug use pattern using World Health Organization prescribing indicators in a tertiary care hospital in Mangalore: A cross-sectional study

Abstract: Background: Irrational prescription being a global problem leading to ineffective, unsafe treatment. Aiming to measure the performance of a health-care provider in key dimension related to appropriate use of drugs, the World Health Organization (WHO) has developed set of core prescribing indicators. Aims and Objectives: The aim of this study is to assess the drug use pattern using WHO core prescribing indicators. Materials and Methods: This was a prospective, cross-sectional study conducted at K.S. Hegde Chari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 6 publications
1
14
1
Order By: Relevance
“…The injection prescribing was lower 0.7% than the WHO standard value, tertiary care hospital of India 8.33%, of western Nepal 3.1% and previous study 5% [11, 18, 25, 26]. The probable reason might be that non-parenteral medication use is easy, cost-effective and convenient in the busy outpatient department while the injection requires trained personnel.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The injection prescribing was lower 0.7% than the WHO standard value, tertiary care hospital of India 8.33%, of western Nepal 3.1% and previous study 5% [11, 18, 25, 26]. The probable reason might be that non-parenteral medication use is easy, cost-effective and convenient in the busy outpatient department while the injection requires trained personnel.…”
Section: Discussionmentioning
confidence: 69%
“…The average number of drugs per encounter was higher (3.2) compared to the standard value 1.6–1.8 and the previous study of the Nepal 2.1 [25, 26]. The average drug per prescription was found low in a teaching hospital in Western Nepal 2.5, tertiary care hospital of India 3.03 and Nigeria tertiary hospital 3.04 [11, 18, 27]. The study showed that most of prescription that is 32.5% had three drugs and 27.5% had four drugs.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Ethical codes were laid down in Ayurveda, which morally abides the physician to maintain conduct that is beneficial for himself, patient and society. Even Vagbhata"s Ashtanga samagraha advocates good conduct, friendly gesture, compassion as distinguishing qualities for physician 18,19 .…”
Section: Ethics In Medical Treatment As Core Of Rationalitymentioning
confidence: 99%